STATE SUPPORT OF SMALL AND MEDIUM ENTREPRENEURSHIP IN RUSSIA AT FEDERAL AND REGIONAL LEVELS - N. Golovetskii; V. Grebenik; I. Kokhanovskaya (Вестник университета)
The current trends in the development of the small and medium-sized business-es in the Russian Federation are considered, and its current state is described. The main directions of state support are highlighted. Despite the relatively high contribution to the provision of employment, small business in terms of such indicators as trade, economic efficiency plays a minor role in modern economic processes in our country. It is noted that the state of small and medium enterprises in the Russian Federation is quite different in different regions, which depends on their specialization, characteristics, availability of jobs, unemployment rate, population structure and other factors. Appropriate, according to the authors, is the assessment of the state of small business in relation to a specific region, and even the city.